Karakteristik Negara Islam; Kajian Awal Ide Negara Abul A’la Maududi - Syafri Gunawan (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2019)
The idea of Islamic state has been well-known among Islamic scholars for years. Abul A’la Maududi is one of Islamic state founders. He stated that a good state is al-Kulafa’ al-Rasyidin’s state of te time. That is a state aims to apply Islamic ideology. Moreover, that should take the following principles; tauhid, risalah, and khilafah. Consequently, Allah Al-mighty is the super power then, where as human is His khalifah in the world.In conclusion, he stated that Islamic state is teo-democracy, ideological and universal state